Social Equity (Women and Youth) Issues to Scale Digital Transformation of Egyptian Agriculture - (ICARDA), International Center for Agricultural Research in the Dry Areas (2024)
The present study provides information about scaling information and communication technologies (ICT) in among women and youth in Egypt. Accordingly, in Egypt, ICT can play a catalytic role in the empowerment of women and youth by: • Expanding economic opportunities through greater access to markets, new forms of income generation and financial services. • Supporting social welfare through improved health service delivery, including reproductive health, comprehensive and up-to-date health and nutrition information, and capacity building opportunities. • Promoting the care economy by helping women maintain work-family balance. • Improving safety at work and otherwise. Providing and linking women to services, mapping, and monitoring cases of gender-based violence (M. Osman, 2019). • Enhancing youth business skills, if supported with adequate training policies, and solving the drastic inability to meet the strict lending requirements of financial institutions.